BUILDING A QUENCHING TEST COUPLED WITH THE APPEARANCE OF ATTENTION DISTRIBUTION FOR HIGH SCHOOL FOOTBALL TEAM PLAYERS - Dr. Mohamed Khalil Ibrahim; Assoc. Prof. Dr. Marwan Khairo Yassin (Proximus Journal Publishing, 2026)
The research aims to: Build a test to measure the skill of suppression coupled with the appearance of attention for high school football team players. Identify the level ofsuppression skill of high school soccer team players. Finding the scores and standardized levels of the test of the suppression skill coupled with the appearance of attention distribution for high school football team players. The researcher used the descriptive method in the survey method to suit it and the nature of the research problem, and the research population consisted of the players of high school teams in the city of Tikrit participating in the high school teams league for the academic year 2024/2025, which are (124) players, and the sample was determined to include all players except the goalkeepers, who are (16) goalkeepers, and the researchers built the test according to the scientific methods of building the tests, and the data was processed by the statistical package (SPSS). The researchers reached the following conclusions: - A test was developed to measure the suppression skill associated with the attention distribution appearance of high school football team players. Standardized degrees and levels of the suppression skill associated with the attention distribution appearance of high school football team players have been established.
Keywords: Construction; Extinguishing; Attention Distribution Appearance